PENGUATAN NILAI-NILAI KEISLAMAN DAN KEMUHAMMADIYAHAN MELALUI PROGRAM GERAKAN JAMA'AH DAN DAKWAH JAMA'AH (GJDJ) DI RUMAH SAKIT MUHAMMADIYAH AHMAD DAHLAN KOTA KEDIRI - Khoirudin, Achmad; Tobroni; Faridi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
Forming and improving the character of the people can be done by strengthening Islamic and Muhammadiyah values ​​in the context of health services, fostering and strengthening attitudes of tolerance and cooperation (ta'awun) between medical personnel, patients and their families, and even the surrounding community. Through the Jama'ah Movement and Jama'ah Dakwah (GJGJ) program, the Muhammadiyah Ahmad Dahlan Hospital in Kediri City is one of Muhammadiyah's charitable efforts in the health sector which is managed with a double track service, namely providing excellent health services combined with spiritual guidance services in the form of instilling scientific and Muhammadiyah values ​​such as ta'awun, tasamuh, tawasuth, tajdid and amar ma'ruf nahy mungkar. This study aims to analyze the effectiveness of the Jama'ah Movement and Jama'ah Dakwah (GJGJ) program in strengthening Islamic and Muhammadiyah values ​​so as to create individuals who are not only intelligent and responsive and have a high sense of caring, but also have a strong spiritual spirit. This study uses a qualitative approach with a case study research design, research data obtained through observation activities, interviews and documentation studies. Implementation of the Jama'ah Movement and Jama'ah Dakwah (GJGJ) program, and its impact on improving the quality of service and community welfare. Thus, this program is expected to be able to improve the spirituality of medical personnel who will give birth to an attitude of enthusiasm, mutual assistance and a deep empathy for the suffering of patients.